Preparation and application of biomass-based hard carbon composite material

By mixing biomass with quaternary ammonium salt solutions and compounding with water-soluble hard carbon precursors, the problems of weak interface binding force and poor component compatibility of biomass composite hard carbon materials are solved, and high platform capacity and first Coulomb efficiency are improved, which significantly improves the electrochemical performance of the material.

CN119774577APending Publication Date: 2025-04-08UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411835134.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing biomass composite hard carbon materials have problems such as weak interface bonding and poor component compatibility, which leads to the material being prone to phase separation during cyclic charging and discharging, poor structural stability and poor battery performance.

Method used

By mixing biomass with quaternary ammonium salt solutions, dissolving and gastrointestinal soluble, the surface reactivity of the biomass is enhanced, and then combined with the water-soluble hard carbon precursor, oxidation stabilization and carbonization treatment are carried out to form a stable interface coupling to improve the uniformity and stability of the material.

Benefits of technology

The high platform capacity and first-time Coulomb efficiency of biomass composite hard carbon materials have been achieved, and the actual electrochemical performance of the material has been improved. The first-time Coulomb efficiency is >90%, and the cycle stability is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774577A_ABST
    Figure CN119774577A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery negative electrode materials, in particular to preparation and application of a biomass-based hard carbon composite material. According to the method, the biomass is treated through the quaternary ammonium salt solution, so that the surface of the biomass is swelled and partially dissolved, the reaction activity end points of the surface of the biomass are expanded, stable interface coupling is generated, and the method can be applied to various biomass raw materials and is high in universality; after oxidation stabilization treatment, carbonization and purification are carried out in a segmented mode, stable interface coupling can be achieved through the wet chemical process, and finally the biomass composite hard carbon material with higher uniformity and stability is prepared. The method is simple in process, low in reagent cost, capable of being treated at normal temperature and easy to produce; the prepared biomass composite hard carbon material is excellent in interface bonding force of different phases, excellent in component compatibility and relatively low in specific surface area; the first coulombic efficiency is gt when the material is used as a sodium-ion battery negative electrode; moreover, the reversible capacity is relatively high, and the actual electrochemical performance of the biomass-based hard carbon is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to the preparation and application of a biomass-based hard carbon composite material. Background Art

[0002] At a critical time in the global energy transition, sodium-ion batteries have become an energy storage system with great development potential due to their abundant resources and low costs, and the research and development of negative electrode materials is one of the core factors that determine their commercialization process. Hard carbon materials, with their unique amorphous microstructure, have stood out as a key research object in the field of sodium negative electrodes. The randomly arranged graphite crystallites, twisted graphene nanosheets and abundant pores inside hard carbon create many sodium ion storage sites with high reversible capacity and low sodium storage potential. Among them, biomass, as a hard carbon precursor, is widely available, green and environmentally friendly, and cost-controlled. Hard carbon derived from coconut shells, bamboo, etc. has emerged, verifying the feasibility of the biomass route and showing certain electrochemical advantages.

[0003] However, it cannot be ignored that the development of biomass hard carbon materials is currently stuck in a bottleneck. Most hard carbons converted from biomass by direct pyrolysis generally have inherent defects such as low closed pore ratio and dense surface defects, which directly lead to unsatisfactory initial efficiency, rapid charge and discharge capacity decay, and poor cycle stability. It is difficult to meet the strict performance standards of large-scale energy storage systems, which seriously restricts its industrialization and promotion.

[0004] Composite modification technology is an important means to effectively improve the performance of biomass hard carbon, aiming to organically integrate the structural and physicochemical characteristics of different precursors to create a synergistic effect. However, the technology currently faces many difficult problems, such as weak interface bonding between different phases, which makes it easy for composite materials to separate during the cycle charge and discharge process, greatly reducing the structural stability; for example, local stress concentration caused by poor compatibility of various components increases the risk of material pulverization and peeling, further compromising the overall performance of the battery.

[0005] Therefore, it is urgent to develop a universal biomass hard carbon composite material modification technology, which can not only consolidate the performance lower limit and unlock the electrochemical potential, but also pave the way for the commercial application of biomass composite hard carbon materials, and will also accelerate the transformation of sodium battery energy storage. Summary of the invention

[0006] In view of the above-mentioned problems or shortcomings, and in order to solve the problems of weak interface bonding force and poor component compatibility among different phases of existing biomass composite hard carbon materials, the present invention provides a preparation and application of a biomass-based hard carbon composite material, which improves the surface reaction activity to produce stable interface coupling, effectively improves the uniformity and stability of biomass composite hard carbon, obtains a higher platform capacity and first coulombic efficiency, and improves the actual electrochemical performance of biomass-based hard carbon.

[0007] To achieve the above purpose, the present invention adopts the following technical solutions

[0008] A method for preparing a biomass-based hard carbon composite material comprises the following steps:

[0009] Step 1, dissolving: Stirring biomass and 40-50wt.% quaternary ammonium salt solution at a solid-liquid ratio of 1g:5-20ml to swell and dissolve the biomass to obtain a mixed solution A; wherein the biomass is lignocellulose-based biomass.

[0010] Step 2, mixing and compounding: dissolving the water-soluble hard carbon precursor in water and adding the mixture A obtained in step 1 to obtain a mixture B, wherein the mass ratio of the water-soluble hard carbon precursor to the biomass is 1 to 5:10.

[0011] Step 3: Oxidation stabilization: After the mixed solution B obtained in step 2 is dried, oxidation stabilization is performed.

[0012] Step 4, pre-carbonization: pre-carbonize the product after oxidation stabilization in step 3; the pre-carbonization conditions are: in an inert gas atmosphere, a temperature of 500-800° C., a heat preservation time of 1-8 hours, and a heating rate of 1-5° C. / min.

[0013] Step 5, pickling: pickle the product after pre-carbonization in step 4 to remove impurities, and then clean it to a neutral pH value.

[0014] Step 6, carbonization: The product obtained in step 5 is subjected to high-temperature carbonization to obtain a biomass-based hard carbon composite material.

[0015] Furthermore, in step 1, the biomass is in the form of powder with a particle size of 200 to 1000 meshes for easy dissolution.

[0016] Furthermore, the quaternary ammonium salt solution in step 1 is a tetrabutylammonium hydroxide solution, which can quickly dissolve cellulose and lignin at room temperature. The chemical reaction activity of the biomass surface is enhanced by swelling or partial dissolution, which is conducive to compounding or cross-linking with the water-soluble hard carbon precursor.

[0017] Furthermore, in step 1, the lignocellulose-based biomass is at least one of coconut shells, bamboo, walnut shells, Cyclobalanopsis glauca and nut shells.

[0018] Furthermore, in step 2, the water-soluble hard carbon precursor is at least one of glucose, polyvinyl pyrrolidone and sucrose.

[0019] Furthermore, the oxidation stabilization in step 3 is specifically: in an aerobic environment, the temperature is 200-400°C, the temperature is kept for 1-6 hours, and the heating rate is 1-10°C / min. Oxidative stabilization can not only further remove the moisture in the mixture, but also cause the lignin, cellulose, hemicellulose and other components in the biomass and the water-soluble hard carbon precursor to undergo preliminary pyrolysis, and enhance the cross-linking effect between the water-soluble hard carbon precursor and the biomass based on the conversion of oxygen functional groups, so as to facilitate the formation of closed cells.

[0020] Furthermore, in step 5, pickling and impurity removal are performed at a solid-liquid ratio of 1g:5-20ml, the acid concentration is 5-20wt.%, and at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrofluoric acid is used.

[0021] Furthermore, the carbonization conditions in step 6 are: in an inert gas atmosphere, the temperature is 900-1500° C., the temperature is kept for 1-4 hours, and the heating rate is 0.5-5° C. / min. Cooling stage: after the heat preservation, the temperature is reduced to 900° C. at a cooling rate of 1-5° C. / min, and then naturally cooled in the furnace.

[0022] The biomass-based hard carbon composite material prepared by the above method has a specific surface area of ​​<5m 2 / g, ash content <1%, crystal plane spacing >0.37nm.

[0023] Application of the above-mentioned biomass-based hard carbon composite material in sodium-ion batteries: As the negative electrode material of sodium-ion batteries, the first coulombic efficiency is >90% and the cycle stability is good.

[0024] In summary, the present invention provides a universal hard carbon composite modification technology, which treats biomass with quaternary ammonium salt solution to make its surface swell and partially dissolve, expands the reactive endpoints on the biomass surface, produces stable interface coupling, and promotes the formation of micro-nanoscale closed-cell structure, which can be applied to a variety of biomass (such as walnut shells, bamboo) raw materials, and has high universality; after oxidation stabilization treatment, carbonization and purification are carried out in sections, and the wet chemical process is conducive to achieving stable interface coupling, and finally a biomass composite hard carbon material with higher uniformity and stability is obtained. The process of the present invention is simple, the reagent cost is low, it can be processed at room temperature, and it is easy to produce; the prepared biomass composite hard carbon material has excellent interface bonding force of different phases, good component compatibility, and has a low specific surface area; when used as the negative electrode of a sodium ion battery, its first coulomb efficiency is>90%, and the reversible capacity is high, which improves the actual electrochemical performance of biomass-based hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a constant current charge and discharge curve diagram of the sample in Example 1 as a negative electrode material for a sodium ion battery.

[0026] Figure 2This is a constant current charge and discharge curve diagram of the sample in Example 2 as a negative electrode material for a sodium ion battery.

[0027] Figure 3 This is a constant current charge and discharge curve of the sample in comparative example 1 as a negative electrode material for a sodium ion battery.

[0028] Figure 4 This is a constant current charge and discharge curve of the sample in comparative example 2 as the negative electrode material of a sodium ion battery.

[0029] Figure 5 This is a cycle diagram of 100 cycles of current density of the sample in Example 1 as a negative electrode material for a sodium ion battery.

[0030] Figure 6 This is the Raman spectrum of the sample in Example 1. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is described more clearly and completely below in conjunction with the accompanying drawings and embodiments.

[0032] Example 1

[0033] A method for preparing a biomass-based hard carbon composite material comprises the following steps:

[0034] Step 1, dissolving: walnut shell powder (200 mesh) and 48wt.% tetrabutylammonium hydroxide are mixed and stirred at room temperature for 6 hours at a solid-liquid ratio of 1g:10ml to obtain a mixed solution A.

[0035] Step 2, mixing and compounding: take glucose accounting for 30% of the mass of walnut shell powder, mix the glucose and ultrapure water in a solid-liquid ratio of 1:5 to form a solution, add it to the sample in step 1 and mix well to obtain a mixed solution B.

[0036] Step 3: Oxidation stabilization: Dry the mixed solution B at 60°C and then oxidize it in a muffle furnace at 250°C for 4 hours.

[0037] Step 4, pre-carbonization: the sample after oxidation stabilization in step 3 was pre-carbonized in 99.999% pure nitrogen at a temperature of 800°C, a pre-carbonization holding time of 2h, and a heating rate of 5°C / min.

[0038] Step 5, pickling: the sample pre-carbonized in step 4 was pickled with 10wt.% hydrochloric acid at a solid-liquid ratio of 1:20 for 6 hours to remove impurities, then washed with pure water and the pH was adjusted to neutral.

[0039] Step 6, carbonization: carbonize the product obtained in step 5 under 99.999% pure nitrogen, raise the temperature to 900°C, and the heating rate is 5°C / min; then increase the temperature from 900°C to 1300°C with a heating rate of 1°C / min, and keep it warm for 2h; then cool it to 900°C at a rate of 3°C / min, and then cool it to room temperature with the furnace. During this period, continue to introduce a protective atmosphere to obtain a biomass-based hard carbon composite material.

[0040] Example 2

[0041] The conditions of Example 1 were kept unchanged, and only the walnut shell powder was replaced with bamboo powder (200 mesh), as Example 2.

[0042] Comparative Example 1

[0043] In this comparative example, the mixed solution A obtained in Example 1 is directly used in step 3 to replace the mixed solution B for the entire experiment, and glucose is not added to prepare the mixed solution B. The other conditions are kept exactly the same as in Example 1. Finally, a universal biomass-based hard carbon composite material is obtained.

[0044] Comparative Example 2

[0045] In this comparative example, the walnut shell powder (200 mesh) of Example 1 is directly used in step 3 to replace the mixed solution B for the entire experiment, and the other conditions remain exactly the same as those of Example 1. Finally, a universal biomass-based hard carbon composite material is obtained.

[0046] Electrochemical performance test:

[0047] Preparation of electrode: The biomass-based hard carbon composite materials obtained in Examples 1 to 2 and Comparative Examples 1 to 2 were used as active materials, respectively, and mixed according to the mass ratio of active material: conductive carbon black (SP): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) of 91:6:1.5:1.5, coated on copper foil with a 100 μm scraper, baked in a vacuum drying oven at 70 ° C for 12 h, and punched with a 14 mm diameter cutter to obtain a surface load of 3.0 to 5.0 mg / cm 2 The negative electrode plates are preferably those with similar surface loadings for assembling batteries.

[0048] Battery assembly and testing: The prepared biomass-based hard carbon composite material (hard carbon) was used as the working electrode, the metal sodium sheet was used as the counter electrode, the glass fiber (Waterman GF / D) was used as the separator, and the electrolyte was 1M NaCF3SO3 in DIGLYME 100Vol%. 2032 button-type sodium ion batteries were assembled in an Ar protective glove box. The battery was tested for constant current charge and discharge at 0.1C in the voltage range of 0.001 to 2.0V, and the results are shown in Table 1.

[0049] Table 1. Electrochemical performance test

[0050] Sample name First discharge specific capacity First coulombic efficiency Platform area capacity Example 1 335.8mAh / g 91.7 223.8mAh / g Example 2 335.1mAh / g 91.5 220.7mAh / g Comparative Example 1 313.3mAh / g 91.0 197.5mAh / g Comparative Example 2 319.5mAh / g 90.7 195.6mAh / g

[0051] The biomass-based hard carbon composite material samples obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were used as negative electrode materials for sodium ion batteries to assemble sodium ion batteries and test them. Figure 1 The sample of Example 1 is used as the negative electrode material of the sodium ion battery, and has a constant current charge and discharge curve at a current density of 0.1C in the voltage range of 0.001 to 2.0V. Figure 2 The sample 2 of this embodiment is used as the negative electrode material of the sodium ion battery, and has a constant current charge and discharge point curve at a current density of 0.1C in the voltage range of 0.001 to 2.0V. Figure 3 The sample of comparative example 1 is used as the negative electrode material of a sodium ion battery, and has a constant current charge and discharge point curve at a current density of 0.1C within a voltage range of 0.001 to 2.0V. Figure 4 The sample of comparative example 1 is used as the negative electrode material of the sodium ion battery, and has a constant current charge and discharge point curve at a current density of 0.1C within a voltage range of 0.001 to 2.0V. Figure 5 The cycle diagram of Example 1 as a negative electrode material for a sodium ion battery is shown, with 100 cycles at a current density of 1C. Figure 6 The Raman spectrum of Example 1 is shown.

[0052] It can be seen from the above examples that walnut shell powder and bamboo powder, as biomass precursors, both show electrochemical properties of improved platform capacity after modification, which confirms the universality and effectiveness of this method. The biomass composite hard carbon sample prepared by the process of the present invention has a platform capacity of ~220mAh / g. Compared with the sample without composite modification treatment, the platform capacity of the obtained biomass-based hard carbon composite material is increased by 20mAh / g (10% improvement rate). The high platform capacity helps to achieve high energy density, highlighting the technical advantages and potential application value of this technology in the field of biomass hard carbon material modification, and is expected to provide new ideas and key technical support for the development of negative electrode materials for sodium ion batteries.

Claims

1. A method for preparing a biomass-based hard carbon composite material, characterized in that: The following steps are involved: Step 1, dissolving: stirring the biomass and 40-50wt.% quaternary ammonium salt solution at a solid-liquid ratio of 1g:5-20ml to swell and dissolve the biomass to obtain a mixed solution A; wherein the biomass is lignocellulose-based biomass; Step 2, mixing and compounding: dissolving a water-soluble hard carbon precursor in water and adding the mixture A obtained in step 1 to obtain a mixture B, wherein the mass ratio of the water-soluble hard carbon precursor to the biomass is 1 to 5:10; Step 3, oxidation stabilization: drying the mixed solution B obtained in step 2, and then performing oxidation stabilization; Step 4, pre-carbonization: pre-carbonize the product after oxidation stabilization in step 3; the pre-carbonization conditions are: in an inert gas atmosphere, a temperature of 500-800° C., a heat preservation time of 1-8 hours, and a heating rate of 1-5° C. / min; Step 5, pickling: pickling the product after pre-carbonization in step 4 to remove impurities, and then cleaning the pH value to neutral; Step 6, carbonization: The product obtained in step 5 is subjected to high-temperature carbonization to obtain a biomass-based hard carbon composite material.

2. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: In the step 1, the biomass is powdered with a particle size of 200 to 1000 meshes.

3. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: The quaternary ammonium salt solution in step 1 is a tetrabutylammonium hydroxide solution.

4. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: In the step 1, the lignocellulose-based biomass is at least one of coconut shells, bamboo, walnut shells, Cyclobalanopsis glauca and nut shells.

5. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: In step 2, the water-soluble hard carbon precursor is at least one of glucose, polyvinyl pyrrolidone and sucrose.

6. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: The oxidation stabilization in step 3 is specifically as follows: in an aerobic environment, the temperature is 200-400° C., the temperature is kept for 1-6 hours, and the heating rate is 1-10° C. / min.

7. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: In the step 5, pickling and impurity removal are performed at a solid-liquid ratio of 1g:5-20ml, and the acid concentration is 5-20wt.%.

8. The method for preparing the biomass-based hard carbon composite material according to claim 1, characterized in that: The carbonization conditions in step 6 are: in an inert gas atmosphere, a temperature of 900 to 1500° C., a heat preservation time of 1 to 4 hours, and a heating rate of 0.5 to 5° C. / min; Cooling stage: After the insulation is completed, the temperature is reduced to 900℃ at a cooling rate of 1-5℃ / min, and then naturally cooled with the furnace.

9. A biomass-based hard carbon composite material, characterized in that: Prepared by any of the methods described in rights 1-8, with a specific surface area of ​​<5m 2 / g, ash content <1%, crystal plane spacing >0.37nm.

10. The biomass-based hard carbon composite material according to claim 9, characterized in that: Used as a negative electrode material for sodium ion batteries.